2019 Global IoT Summit (GIoTS) 2019
DOI: 10.1109/giots.2019.8766430
|View full text |Cite
|
Sign up to set email alerts
|

Security Issues in Internet of Things: Vulnerability Analysis of LoRaWAN, Sigfox and NB-IoT

Abstract: One of the key enablers of an increased Internet of Things (IoT) roll-out is Low-Power Wide Area Network (LP-WAN)-a family of technologies tailored for resilient and energy-efficient communication of thousands of devices over large distances (even up to 100km). Under the pressure from both the business and the society to provide ubiquitous connectivity as soon as possible, new IoT deployments are conducted with haste and often by inexperienced people. Consequently, the aspect of communication security traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The analysis of LPWAN data integrity have been a major topic in the literature as major LPWAN standards are known to be highly vulnerable to integrity attacks. In an analysis of LPWAN integrity vulnerabilities, the authors in [ 15 , 69 ] cautioned that Sigfox is highly vulnerable to replay attacks and they strongly advised against its deployment for critical applications. However, the authors in [ 69 ] advised that better replay protection must be integrated at a higher layer by end users, thus minimizing the already small payload size.…”
Section: Lpwan Security Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of LPWAN data integrity have been a major topic in the literature as major LPWAN standards are known to be highly vulnerable to integrity attacks. In an analysis of LPWAN integrity vulnerabilities, the authors in [ 15 , 69 ] cautioned that Sigfox is highly vulnerable to replay attacks and they strongly advised against its deployment for critical applications. However, the authors in [ 69 ] advised that better replay protection must be integrated at a higher layer by end users, thus minimizing the already small payload size.…”
Section: Lpwan Security Analysismentioning
confidence: 99%
“…In an analysis of LPWAN integrity vulnerabilities, the authors in [ 15 , 69 ] cautioned that Sigfox is highly vulnerable to replay attacks and they strongly advised against its deployment for critical applications. However, the authors in [ 69 ] advised that better replay protection must be integrated at a higher layer by end users, thus minimizing the already small payload size. Similarly, the authors in [ 17 ] explained that Weightless-P network are also prone to replay and wormhole attacks.…”
Section: Lpwan Security Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Navarro-Ortiz et al [53] focuses on the safety of the LoRaWAN technology and describes the possibility of its improvement on the HW level. The analysis of LoraWAN, Sigfox, and NB-IoT vulnerability is conducted in [54]. This work [55] describes the concept of Small Cell Cloud (SCC) composed of multiple Cloud-enabled Small Cells (CeSCs), which provide radio connection for mobile User Equipment (UE), such as smart-phones or wearables.…”
Section: Related Work and Solutionsmentioning
confidence: 99%
“…Nevertheless, the literature focuses on improving the current protocols, proposing new features or solving vulnerabilities. For instance, Zhang et al [ 31 ] and Laurentiu et al [ 32 ] reported security flaws in BLE and LoRaWAN, Sigfox and NB-IoT, respectively. Mao et al [ 33 ] proposed a security configuration strategy for IEEE 802.15.4 that adapts its level depending on the network security threats, service requirements and harvested energy.…”
Section: Introductionmentioning
confidence: 99%